Ответы и объяснения

2013-12-18T05:37:19+00:00
(cos(x)+sin(x))^2=cos(2x)
cos^2(x)+2*sin(x)*cos(x)+sin^2(x)=cos(2x)
cos(2x)=cos^2(x)-sin^2(x)
cos^2(x)+2*sin(x)*cos(x)+sin^2(x)-(cos^2(x)-sin^2(x))=0 косинусы в квадрате сокращаются, так как cos^2(x)-cos^2(x)=0
2*sin^2(x)+2*sin(x)*cos(x)=0 разделим обе части на cos^2(x) получим
2tg^2(x)+2tg(x)=0
tg(x)(2tg(x)+2)=0
tg(x)=0 или 2tg(x)+2=0
x=arctg(o)+пи*n,(n принадлежит Z)
x=пи*n,(n принадлежит Z)
2tg(x)+2=0
tg(x)=-2/2
tg(x)=-1
x=arctg(-1)+пи*n, (n принадлежит Z)
x=-пи/4+пи*n,(n принадлежит Z)
Ответ: -пи/4+пи*n;пи*n;